Peningkatan Kualitas Outcome Program Keahlian Teknik Sepeda Motor dengan Menggunakan Model â€œMega-Proâ€ - Nurwati, Tri; Basrowi, Basrowi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
The purpose of this study is to: describe the best practice of conducting management model of TSM skill program using Mapping, Exploring, Goal setting, Assessing, PROmoting (MEGA-PRO) concept and prove that management model of TSM skill program using MEGA-PRO concept is able to reduce waiting time students to have income. The method used is qualitative research. The research was conducted at SMK N 8 Purworejo in Central Java. Data were collected by using participatory observation, interviews, and documentation. Data were analyzed by using a four-stage analysis of qualitative data that includes data collection, data reduction, data classification, and conclusion. Based on the results of data analysis can be concluded that: (1) best practice of conducting management model of TSM skill program using MEGA-PRO model is able to improve the knowledge, skill and studentsâ€™ attitude, and (2) management of TSM program using MEGA-PRO model is able to reduce waiting time students to have income.